Purification and characterization of Antarctic krill chitinase and its role on free fluoride release from Antarctic krill cuticle - JI,Wei (2022)
Abstract To investigate factors that influence free fluoride release in Antarctic krill cuticle, the enzyme properties of a chitinase from Antarctic krill were analyzed to identify its role on free fluoride release from Antarctic krill cuticle. The chitinase was purified by ammonium sulfate precipitation,ion and gel chromatography, and identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). The molecular mass of the chitinase purified from Antarctic krill was 59.0 kDa and its peptide sequences were similar to chitinase precursor sequences from Penaeus vannamei. The optimal pH of the chitinase was pH 6.5 and temperature 45 °C and exhibited high stability within pH 5.0-6.0 and temperatures below 35 °C. The chitinase activity was increased by Ca2+ and Mg2+, while inhibited by Fe2+, Cu2+ and Co2+. The purified chitinase had Km and Vmax values of 5.88 mmol/L and 2.11 μmol/min·mL, respectively. The endogenous chitinase purified from Antarctic krill could degrade chitin fibers and induced the release of free fluoride from Antarctic krill cuticle. Under experimental conditions, the free fluoride release law in Antarctic krill cuticle can be described by equation: C W = 1 − 0.98 e − 0.0111 t − 0.02 e 0.15 t × 175.52 + 10.80.